Current application of MOFs based heterogeneous catalysts in catalyzing transesterification/esterification for biodiesel production: A review. (1st February 2021) - Ma, Xiaoling; Liu, Fengsheng; Helian, Yaxin; Li, Chaorui; Wu, Zhongjie; Li, Hui; Chu, Huijun; Wang, Yongbo; Wang, Yangyang; Lu, Wanpeng; Guo, Min; Yu, Mingzhi; et al.
Graphic abstract: Highlights: MOFs are widely used in heterogeneous catalytic synthesis for biodiesel production. MOFs derivate inherits the promising merit from pristine MOFs. Active site is anchored with MOFs or MOFs derivate via covalent and coordinate bond. Macromolecule active site could be locked in MOFs via the micro size cage. Abstract: Biodiesel is a green and renewable energy, which is supposed to be a promising substitute to fossil diesel. Normally, biodiesel is produced via transesterification/esterification with assistance of homogeneous or heterogeneous catalyst. However, homogeneous catalyst cannot be recovered and reused. In particular, the downstream purification is needed resulting in large number of wastewater. Thereby, heterogeneous catalysts are put forward to address these above problems. The catalytic activity of heterogeneous catalyst (alkaline, acid, and enzyme) is restricted by the active site dispersity, available active site amount, and catalytic stability. With regard to this, supporting active site on carrier is a feasible technology to improve catalytic performance. Metal organic frameworks (MOFs) are a special class of coordination polymers, which are self–assembled by metal ion and organic ligand with topological structure. The promising merits of huge porosity, uniform pore size, controllable functional groups, and structural tenability of MOFs are highly desirable in synthesizing catalyst for transesterification/esterification. This paper reviews the current application of MOFs in catalyzing transesterification/esterification, which is involved with catalytic mechanism, MOFs types, especially the MOFs catalyst and MOFs derivate based catalysts. Meanwhile, the reusability of MOFs based catalyst are further analyzed. Thereafter, the effect of transesterification/esterification parameters on catalytic performance are comprehensively summarized. The future perspectives for MOFs application in biodiesel production are also discussed.